THE ROLE AND IMPORTANCE OF INVESTMENT ATTRACTIVENESS IN IMPROVING THE BANKING AND FINANCIAL SECTORS OF THE MARKET ECONOMY - Ruzimatov Sanjarbek Qosimjon ugli (Galaxy International Interdisciplinary Research Journal, 2024)
Investment attractiveness is crucial to ensuring economic growth, stability and development of the banking and financial sector in a market economy. Investment attractiveness is a key factor in strengthening the banking sector, as it attracts both domestic and foreign investors. Investment attractiveness means the ability to attract investments based on economic potential, stability and market or industry development prospects. The investment attractiveness of the banking sector may be influenced by several factors, including regulatory framework, economic stability, profitability and general ease of doing business. This article defines investment attractiveness as the way in which investors direct their resources to financial institutions and the banking sector within a given market, the right allocation and many other types of investment activities.